Salvage robotic-assisted radical prostatectomy after targeted high-intensity focused ultrasound: a single-center study on feasibility, oncological and functional outcomes - Cella, Ludovica; Fasulo, Vittorio; Moretto, Stefano; Beatrici, Edoardo; Piccolini, Andrea; Avolio, Pier Paolo; Maffei, Davide; Contieri, Roberto; Tallari, Alessandro; Mallia, Valerio; Uleri, Alessandro; Saita, Alberto; et al. (Frontiers in Oncology, 2026)
Background/ObjectivesTargeted High-Intensity Focused Ultrasound (HIFU) is an emerging treatment option for localized prostate cancer (PCa), aiming to balance oncological control with functional preservation. However, data on the feasibility and outcomes of salvage robotic-assisted radical prostatectomy (sRARP) after targeted HIFU remain limited. This study aimed to evaluate feasibility, functional and early oncological outcomes of sRARP in this specific setting.MethodsAmong 112 men treated with targeted HIFU for localized prostate cancer, 15 underwent sRARP between June 2022 and June 2025. The primary outcome was surgical feasibility and safety, assessed by conversion rate, operative time, nerve-sparing approach, lymphadenectomy, positive surgical margins (PSM) at frozen section and final pathology, and intraoperative complications. Secondary outcomes included urinary continence (full or social continence at 1 year), erectile function (with or without phosphodiesterase type 5 inhibitors at 1 year), PSA levels at 45 days and one year after surgery, and postoperative complications.ResultsAll procedures were completed robotically without intraoperative complications or conversions. Bilateral nerve-sparing was performed in 13 patients (87%). PSM were found in three (20%) patients at frozen section and in two patients (13%) at final pathology; one patient (11%) had lymph node metastases. Early complications occurred in three patients (20%), with only one Clavien Dindo grade ≥3 event. At 1-year follow-up, one patient (8%) had PSA >0.2 ng/mL; nine patients (75%) were continent and six (50%) reported preserved erectile function. The median follow-up was 14 months (IQR 10.8–16.5; 95% CI).ConclusionssRARP after targeted HIFU is feasible and safe, with favorable early oncological and functional outcomes. These findings suggest that targeted HIFU may be a viable option in selected patients, without compromising future curative strategies in case of recurrence.